Accumulation of gene copy number variations during the early phase of free‐spawning abalone speciation. Issue 2 (17th February 2023) - Hirase, Shotaro; Sekino, Masashi; Hara, Motoyuki; Kikuchi, Kiyoshi
Abstract: The genetic basis of speciation in free‐spawning marine invertebrates is poorly understood. Although gene copy number variations (GCNVs) and nucleotide variations possibly trigger the speciation of these organisms, empirical evidence for such a hypothesis is limited. In this study, we searched for genomic signatures of GCNVs that may contribute to the speciation of Western Pacific abalone species. Whole‐genome sequencing data suggested the existence of significant amounts of GCNVs in closely related abalones, Haliotis discus and H. madaka, in the early phase of speciation. In addition, the degree of interspecies genetic differentiation in the genes where GCNVs were estimated was higher than that in other genes, suggesting that nucleotide divergence also accumulates in the genes with GCNVs. GCNVs in some genes were also detected in other related abalone species, suggesting that these GCNVs are derived from both ancestral and de novo mutations. Our findings suggest that GCNVs have been accumulated in the early phase of free‐spawning abalone speciation. Abstract : Although gene copy number variations (GCNVs) and nucleotide variations possibly trigger the speciation of free‐spawning marine invertebrates, empirical evidence for such a hypothesis is limited. Our findings suggest that the accumulation of GCNVs contributes to the speciation of free‐spawning marine invertebrates during the early phase.